The Power of Babble. - HELLAND, PAT (Communications of the ACM, 2016)
The article discusses the emerging and increasing common metadata for interoperability of computer systems. Topics include efforts within the computing industry to establish standard forms of communication, the tendency for translation between two data representations to be lossy and not successfully move all of the information from one form to another, and the creation of the artificial language Esperanto in 1887 to achieve a common shared natural language for all people.